2010
DOI: 10.1073/pnas.1004745107
|View full text |Cite
|
Sign up to set email alerts
|

A genetically modulated, intrinsic cingulate circuit supports human nicotine addiction

Abstract: Whole-genome searches have identified nicotinic acetylcholine receptor α5-α3-β4 subunit gene variants that are associated with smoking. How genes support this addictive and high-risk behavior through their expression in the brain remains poorly understood. Here we show that a key α5 gene variant Asp398Asn is associated with a dorsal anterior cingulate-ventral striatum/extended amygdala circuit, such that the "risk allele" decreases the intrinsic resting functional connectivity strength in this circuit. Importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
131
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(141 citation statements)
references
References 58 publications
9
131
1
Order By: Relevance
“…Our data showed the presence of reduced bCBV in the cingulated gyrus, prefrontal cortex, orbitofrontal cortex, as well as in striatal and hippocampal areas of cocaine SA subjects. The frontostriatal effect is in excellent agreement with clinical neuroimaging research of cocaine addiction, where reduced frontal and striatal activities have been consistently observed (Strickland et al, 1993;Tumeh et al, 1990;London et al, 1999;Volkow et al, 1992Volkow et al, , 1988 and found to correlate with the cognitive impairments, compulsion, and loss of inhibitory control over drug taking that may lead to relapse (Goldstein et al, 2010;Kalivas et al, 2005;Kalivas, 2004;Hong et al, 2010;Strickland et al, 1993). Importantly, cognitive deficits have been observed in rats allowed extended (but not limited) access to cocaine (Briand et al, 2008;George et al, 2007), a phenomenon that involved working memory and sustained attention tasks (two prefrontal cortex-dependent tasks) as well as object recognition measures (a hippocampus-dependent task).…”
Section: Altered Brain Function After Cocaine Self-administrationsupporting
confidence: 66%
“…Our data showed the presence of reduced bCBV in the cingulated gyrus, prefrontal cortex, orbitofrontal cortex, as well as in striatal and hippocampal areas of cocaine SA subjects. The frontostriatal effect is in excellent agreement with clinical neuroimaging research of cocaine addiction, where reduced frontal and striatal activities have been consistently observed (Strickland et al, 1993;Tumeh et al, 1990;London et al, 1999;Volkow et al, 1992Volkow et al, , 1988 and found to correlate with the cognitive impairments, compulsion, and loss of inhibitory control over drug taking that may lead to relapse (Goldstein et al, 2010;Kalivas et al, 2005;Kalivas, 2004;Hong et al, 2010;Strickland et al, 1993). Importantly, cognitive deficits have been observed in rats allowed extended (but not limited) access to cocaine (Briand et al, 2008;George et al, 2007), a phenomenon that involved working memory and sustained attention tasks (two prefrontal cortex-dependent tasks) as well as object recognition measures (a hippocampus-dependent task).…”
Section: Altered Brain Function After Cocaine Self-administrationsupporting
confidence: 66%
“…For example, plasma concentrations of varenicline could be measured in individuals prescribed this medication 34 to test for the effect of functional OCT2 alleles on medication plasma levels, to test association between medication plasma levels and prospective abstinence, and on the influence of the functional OCT2 alleles on prospective abstinence, as has been reported for the bupropion metabolite hydoxybupropion and CYP2B6 variation. 81 Effects of the functional OCT2 allele on brain structure and function may be observable, given prior studies that have identified effects on brain structure 82 and function 83 of cholinergic 47,84 and dopaminergic 40,85 alleles that influence smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of preclinical animal models to nicotine dependence is questioned because their predictive validity is considered poor (Hong et al, 2010). In spite of this, preclinical animal models of nicotine seeking have been proved useful, as they have helped in understanding the mechanisms underlying nicotine seeking.…”
mentioning
confidence: 99%